2014
DOI: 10.1037/lhb0000086
|View full text |Cite
|
Sign up to set email alerts
|

A psychometric examination of treatment change in a multisite sample of treated Canadian federal sexual offenders.

Abstract: In the present study, we examined the degree of change and predictive accuracy of a number of well-known psychological self-report measures intended to identify treatment targets for sexual offenders. Participants included 392 federally incarcerated sexual offenders who participated in low, moderate, or high intensity sexual offender programs offered within penitentiaries under the jurisdiction of the Correctional Service of Canada. These men were followed in the community for an average of 5.42 years postrele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 60 publications
3
42
3
2
Order By: Relevance
“…There are also some clear indications that the lack of clinical elevation in the self-report measures could be attributed to contextual differences (also see Olver, Kingston, Nicholaichuk, & Wong, 2014). Research by Hornsveld, Kraaimaat, Bouwmeester, Polak, and Zwets (2014) demonstrated, within a similar inpatient sample, that these inpatients barely show any aggressive behavior after admission and that this effect remained stable over a follow-up period of 3 years.…”
Section: Discussionmentioning
confidence: 94%
“…There are also some clear indications that the lack of clinical elevation in the self-report measures could be attributed to contextual differences (also see Olver, Kingston, Nicholaichuk, & Wong, 2014). Research by Hornsveld, Kraaimaat, Bouwmeester, Polak, and Zwets (2014) demonstrated, within a similar inpatient sample, that these inpatients barely show any aggressive behavior after admission and that this effect remained stable over a follow-up period of 3 years.…”
Section: Discussionmentioning
confidence: 94%
“…For example, among studies examining change in sex offenders attending rehabilitation, one study reported that change scores predicted recidivism beyond static risk scores (Beggs & Grace, 2011), but this finding is balanced by non-significant results in both large sample (Barnett, Wakeling, Mandeville--Norden, & Rakestrow, 2013;Wakeling, Beech, & Freemantle, 2013) and small sample programs (Nunes, Pettersen, Hermann, Looman, & Spape, 2014;Pettersen et al, 2015;Woessner & Schwedler, 2014). Similarly, Olver, Kingston, Nicholaichuk, and Wong (2014) found only a few subscales predicted recidivism in their sample of sex offenders, while most pre--post measures did not; however, change in sexual deviance was a consistent predictor across two samples (Olver, Beggs Christofferson, et al, 2014). Also, one study with violent offenders found changes in attitudes and anger did not predict post--program recidivism (Klepfisz, O'Brien, & Daffern, 2014), whereas change scores in other programs predicted violent recidivism (De Vries Robbé, de Vogel, Douglas, & Nijman, 2015;Lewis, Olver, & Wong, 2012;Novaco & Taylor, 2015).…”
Section: Meta--reviews Of Intra--individual Change During Rehabilitationmentioning
confidence: 99%
“…Blumenthal et al (1999) ont observé que les agresseurs sexuels d'enfants et les agresseurs sexuels d'adultes sont similaires sur le plan des distorsions à l'égard du viol. D'autres auteurs (Arkowitz et Vess, 2003 ;Olver, Kingston, Nicholaichuk et Wong, 2014) ont même observé davantage de distorsions à l'égard du viol chez les agresseurs sexuels d'enfants comparativement aux agresseurs d'adultes. La notion du droit à la sexualité réfère à la croyance que l'individu a « tous les droits » à propos de la sexualité et qu'il est justifié de combler ses besoins sexuels (Hanson, Gizzarelli et Scott, 1994).…”
Section: Distorsions Cognitives Et Croyances Erronéesunclassified